Effect of consecutive rare codons on the recombinant production of human proteins in Escherichia coli. Issue 2 (11th September 2019) - Correddu, Danilo; Montaño López, José de Jesús; Angermayr, S. Andreas; Middleditch, Martin J.; Payne, Leo S.; Leung, Ivanhoe K. H.
Abstract: In Escherichia coli, the expression of heterologous genes for the production of recombinant proteins can be challenging due to the codon bias of different organisms. The rare codons AGG and AGA are among the rarest in E. coli . In this work, by using the human gene RioK2 as case study, we found that the presence of consecutive AGG‐AGA led to a premature stop, which may be caused by an event of −1 frameshift. We found that translational problems caused by consecutive AGG‐AGA are sequence dependent, in particular, in sequences that contain multiple rare AGG or AGA codons elsewhere. Translational problems can be alleviated by different strategies, including codon harmonization, codon optimization, or by substituting the consecutive AGG‐AGA codons by more frequent arginine codons. Overall, our results furthered our understanding about the relationship between consecutive rare codons and translational problems. Such information will aid the design of DNA sequence for the production of recombinant proteins.